How do English Teachers Apply Layered Vocabulary Teaching Strategies in Indonesian Junior Secondary EFL Classroom? - Maemuna Muhayyang; Nur Syafa Malik; Muh. Fakhrul Armas (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This qualitative descriptive study explores how English teachers apply vocabulary teaching strategies in EFL classrooms at the junior secondary level. Data were collected through semi-structured interviews with three experienced English teachers at SMP Negeri 1 Wasuponda, South Sulawesi, Indonesia. The findings reveal that teachers employed a diverse repertoire of strategies encompassing de-contextualizing (word lists, flashcards, dictionary use), semi-contextualizing (word grouping, association, imagery, keyword method, physical response, semantic mapping), fully contextualizing (reading, listening, speaking, writing), and adaptable approaches (structured reviewing). These strategies were implemented through both planned instruction—deliberate preparation of materials and activities—and incidental teaching, in which teachers spontaneously explained unfamiliar words arising during classroom interaction. Although implementation varied according to individual preferences and contextual demands, the integration of multiple strategies effectively supported students’ vocabulary acquisition, retention, and meaningful use. The study underscores the pedagogical value of flexible, layered strategies in resource-variable multilingual settings and carries important implications for teacher professional development, curriculum design aligned with Indonesia’s Merdeka Curriculum, and policy initiatives that promote strategic sequencing and learner autonomy in outer-circle EFL contexts.